2019
DOI: 10.18174/472638
|View full text |Cite
|
Sign up to set email alerts
|

iSQAPER task WP 3.3 soil quality indicators : Influence of soil type and land management on chemical, physical and biological soil parameters assessed visually and analytically

Abstract: Influence of soil type and land management on chemical, physical and biological soil parameters assessed visually and analytically. Output of EU project iSQAPER, work package 3, task 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Bottinelli et al (2023) attribute the higher bulk density in reduce tillage in the 12-20 cm layer to a vermicular microstructure (Verrecchia et al, 2021), created by earth worm activity. Higher earthworm abundance was found by Hoek et al (2019) in reduced tillage systems. Also Rücknagel et al (2017) found higher bulk density in the lower topsoil for conservation tillage, compared to conventional tillage, in seven medium-and long-term soil tillage experiments in Central Europe.…”
Section: 5mentioning
confidence: 87%
See 2 more Smart Citations
“…Bottinelli et al (2023) attribute the higher bulk density in reduce tillage in the 12-20 cm layer to a vermicular microstructure (Verrecchia et al, 2021), created by earth worm activity. Higher earthworm abundance was found by Hoek et al (2019) in reduced tillage systems. Also Rücknagel et al (2017) found higher bulk density in the lower topsoil for conservation tillage, compared to conventional tillage, in seven medium-and long-term soil tillage experiments in Central Europe.…”
Section: 5mentioning
confidence: 87%
“…The presence and diversity of earthworms was measured from 2009 till 2013 by a PhD student (Crittenden et al, 2014) and in 2016 by Hoek et al (2019). Hoek et al (2019) Reduced soil tillage can also have disadvantages, like difficulties with seedbed preparation, especially for small seeded crops.…”
Section: Biological Soil Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…and animal health'' and by Gregorich and Action, 1995, as ''soil capacity to support crop growth without resulting in soil degradation or otherwise harming the environment''. ''Soil parameters which reflect soil quality and soil-based ecosystem services'' are described as ''Soil quality indicators" (Hoek et al, 2019). The physical quality evaluation of the main soils (chernozems, luvisols) from Dolj county was made by Manea et al, 2022. The soil chemical quality in relation with crop production is to provide nutrients (Heil and Sposito 1997).…”
mentioning
confidence: 99%
“…The soil chemical properties are ''mostly used to measure soil fertility and health'' (Sainju and Lipzin, 2022). For the evaluation of soil quality, the most studied chemical properties are: soil reaction, calcium-carbonate, cation exchange capacity, soil salinity, exchangeable sodium percentage, soil organic matter, total nitrogen, extractable form of phosphorus and potassium content (Janků et al, 2022, Sainju and Lipzin, 2022, Hoek et al, 2019, Takoutsing et al, 2016, Toth et al, 2016, Oliver et al, 2013, Toth et al, 2013, Arshad and Coen., 1992. The objective of this paper is to assess the impact of agricultural practices on chemical quality of some Chernozems and Luvisols from Dolj county.…”
mentioning
confidence: 99%